Management of Post Tumor Resection in Inferolateral Eyelid using Periosteal Flap and Canthoplasty Technique – A Case Report: Poster Presentation - Case Report - Resident - CLARA VALENTINA; Putu Yuliawati; Ni Made Laksmi Utari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eyelid defect repair goals are providing supportive connecting tissue and functional mucosal epithelium. Posterior lamellar reconstruction for tumor resection defect is still challenging. In this case, lower eyelid reconstruction can be accomplished by elevation and rotation of periosteal flap as posterior lamella. Case Illustration : A 68-years-old male came with inferolateral eyelid mass of Left Eye (LE) that was increasing in last 3 months. On LE examination found solitary cystic cutaneous lesion in inferior palpebra near lateral canthal, sized7x5mm, fixated, regular, and chewy consistency. Anterior of mass has same color as adjacent skin with hyperpigmentation lesion and posterior side was translucent with telangiectasia. He was suspected with LE ductal dd epidermoid cyst. Discussion : Periosteal flap and canthoplasty is procedure to repair inferolateral eyelid defect that are large to be closed primarily, however it requires adequate lateral canthal skin and tarsal plate. Posterior lamellais restored to create connective tissue framework, proper contour, and vertical canthal height. Tumor was removed and preperiosteal plan inferior to inferior orbital rim was dissected. The anterior lamella then transposed superiorly to make sure it will cover posterior lamellar reconstruction. Periosteal flap from lateral canthal tendon of infraorbital margin was harvested, flap was crossed to form sharp canthal angle and sutured to tarsal edges of lower eyelids as posterior lamella. A week later, LE showed natural contour and good function without eyelid malposition. Conclusion : Periosteal flap as posterior lamella reconstruction of eyelid defects is effective and efficient to repair eyelid defect due to its simplicity, reliability, and low risk complication.